Are Literary Languages Artificial?: The Case of the Aramaic of the Zohar - Siegal, Elitzur A. Bar-Asher (Aramaic studies, 2020)
Few studies have focused on the Aramaic of the Zohar, and to this day, only one of these presents a completed grammatical analysis. Scholars have dealt at large, however, with the question of whether the Aramaic of the Zohar is artificial or not. I briefly review the history of the literature around this question, then propose my own criteria to examine whether a language of a given text is indeed artificial. Finally, I put this methodology into practice, as I investigate the nature of Zoharic Aramaic by examining specific linguistic phenomena in the relevant corpus.